Alerts in mobile healthcare applications requirements and pilot study. - Kafeza, E.
Recent advances in mobile technologies have greatly extended traditional communication technologies to mobile devices. At the same time, healthcare environments are by nature "mobile" where doctors and nurses do not have fixed workspaces. Irregular and exceptional events are generated in daily hospital routines, such as operations rescheduling, laboratory/examination results, and adverse drug events. These events may create requests that should be delivered to the appropriate person at the appropriate time. Those requests that are classified as urgent are referred to as alerts . Efficient routing and monitoring of alerts are keys to quality and cost-effective healthcare services. Presently, these are generally handled in an ad hoc manner. In this paper, we propose the use of a healthcare alert management system to handle these alert messages systematically. We develop a model for specifying alerts that are associated with medical tasks and a set of parameters for their routing. We design an alert monitor that matches medical staff and their mobile devices to receive alerts, based on the requirements of these alerts. We also propose a mechanism to handle and reroute, if necessary, an alert message when it has not been acknowledged within a specific deadline.
Keywords: Adverse drug event; Alert monitoring; Communication technology; Efficient alert routing; Exception handling; Healthcare alert management system; Hospital routine; Mobile device; Mobile healthcare application; Monitor requirements engineering